Efektivitas Pembelajaran Cooperative Learning untuk Meningkatkan Keaktifan Siswa pada Mata Pelajaran Aqidah Kelas XI di SMAN 1 Purwakarta - Farah Dita Azhari; Nan Rahminawati; Nurul Afrianti (Bandung Conference Series: Islamic Education, 2024)
Abstract. This research aims to determine the effectiveness of cooperative learning in increasing student activity in Aqidah learning at SMAN 1 Purwakarta. The approach used in this research is a quantitative approach with quasi-experimental research methods. The subjects of this research were all 33 students of class XI MIPA 4. The data analysis technique was carried out using the Paired Sample T-Test. Based on the results of data processing, research results were obtained by distributing questionnaires to 33 students before the cooperative was implemented, resulting in a mean student score of 34.24 with the mean score in the category of class XI MIPA 4 students being quite active in learning activities. cooperative learning in Aqidah learning, in which students carry out learning together in groups to discuss, collaborate and complete group assignments and then present the results of group discussions and collaboration. The results of testing using the paired sample t test showed differences in pre-test and post-test scores, after implementing cooperative learning, the mean post-test score was 50.64. These results show that the learning method using cooperative learning can increase student activity in the Class XI Aqidah Akhlak subject at SMAN 1 Purwakarta. The amount of increase is 16.4. Through the results of the paired t-test, a significance value (2-tailed) was obtained of 0.00, which means Sig < 0.05, which means there is a significant difference between the average value of the pre-test and post-test before implementing cooperative learning. and after implementing cooperative learning. Abstrak. Abstrak. Penelitian ini bertujuan untuk mengetahui efektivitas cooperative learning terhadap peningkatan keaktifan siswa dalam pembelajaran Aqidah di SMAN 1 Purwakarta. Pendekatan yang digunakan adalah pendekatan kuantitatif dengan metode penelitian quasi eksperimen. Adapun subjek penelitian ini adalah seluruh siswa kelas XI MIPA 4 yang berjumlah 33 orang. Teknik analisis data dilakukan dengan uji Paired Sample T-Test. Berdasarkan hasil pengolahan data diperoleh hasil penelitian dengan menyebarkan angket kepada 33 siswa sebelum cooperative diterapkan didapatkan hasil nilai mean siswa sebesar 34,24 dengan mean nilai tersebut kategori siswa kelas XI MIPA 4 cukup aktif didalam kegiatan pembelajaran. Cooperative learning dalam pembelajaran Aqidah yang dalam pelaksanaan pembelajaran siswa bersama dengan berkelompok berdiskusi, bekerjasama dan menyelesaikan tugas kelompok lalu mempresentasikan hasil diskusi dan kerjasama berkelompok. Hasil dari pengujian melalui uji paired sample t test didapatkan hasil perbedaan nilai pre-test dan post-test, setelah diterapkan cooperative learning didapatkan hasil mean nilai post-test sebesar 50,64. Hasil tersebut menunjukkan bahwa metode pembelajaran dengan cooperative learning dapat meningkatkan keaktifan Siswa pada Mata Pelajaran Aqidah Akhlak Kelas XI di SMAN 1 Purwakarta. Adapun besaran peningkatannya ialah sebesar 16,4. Melalui hasil uji-paired t-test didapatkan nilai Signifikasi (2-tailed) sebesar 0,00 yang artinya Sig.< 0,05 yang artinya terdapat perbedaan yang signifikansi antara nilai rata-rata pre-test dan post-test sebelum diterapkan cooperative learning dan setelah diterapkan cooperative learning.